The generalized force-velocity relationship explains why the preferred pedaling rate of cyclists exceeds the most efficient one - Kohler, G.; Boutellier, U. (European Journal of Applied Physiology, 2005)
The most efficient pedaling rate (lowest oxygen consumption) at a workload of 50-300 W has been reported to be in the range of 42-60 rpm. By contrast, most competitive cyclists prefer a pedaling rate of more than 90 rpm. The reason for this difference is still unknown. We assume that the high pedaling rate preferred by cyclists can be explained by the inherent properties of muscle fibers. To obtain statements which do not depend on muscle's cross-section and length, we generalized Hill's characteristic equations where muscle force and heat liberation are related to shortening velocity. A pedaling rate of f (etamax) yields to maximal efficiency, whereas the higher pedaling rate f (Pmax) leads to maximal power. The ratio f (Pmax)/f (etamax) between these two pedaling rates ranges from 1.7 to 2.4, and it depends on the muscle's fiber-type composition. In sprints and competitions of very short duration, f (Pmax) is more advantageous because energy supply is not the predominant limiting factor. The price to be paid for the most powerful pedaling rate is lower efficiency and higher energy cost. In longer exercises, economy is more important and the optimal pedaling rate shifts toward f (etamax). We conclude that the optimal pedaling rate, representing the fastest race performance, is not fixed but depends on race duration; it ranges between f (etamax) and f (Pmax). Our results are not only of interest for competitive cyclists but also for investigations using cycle ergometers: maximum power might not be reached by using a pedaling rate near the most efficient one.